Strategy-proofness and Fixed-price Allocation of Indivisible Goods - a Characterization Proof - Lars-Gunnar Svensson (Lund University, School of Economics and Management, Department of Economics, 2002)
In this paper we considered the classical Shapley-Scarf (1974) "house allocation model", where in addition there is a perfectly divisible good (money). The problem is to characterize all strategy-proof, nonbossy and individually rational allocation mechanisms. The finding is that only a fixed-price allocation mechanism is consistent with these presumptions. Miyagawa (2001) first proved this result. Here we give an alternative and comparatively short proof of the characterization result.
Keywords: C71; C78; D71; D78; 330; Strategy-proof; Indivisible object; Housing market